Validity and reliability of reactive agility measurements of tennis performance - Wisnu Nugroho, T.; Alim, A.; Fauzi, H. Y. (International Journal of Human Movement and Sports Sciences, 2022)
Reactive agility measurement tool recently has become one of the important issues in the physical training for tennis performance. Therefore, finding a valid and reliable reactive agility measuring instrument for tennis performance is needed. This study aimed to do a validity and reliability test of the reactive agility measuring instrument for tennis performance. This study used a mixed-methods approach. The seven experts participants were determined by the criteria of an evaluation expert and a tennis expert, or both. This study had three stages. The first was document analysis (international journal). It is used to develop a construction design for the reactive tennis agility measuring instrument. The second stage was content validation. The participants were seven experts. Then, the data collection technique used the Delphi technique. The research instrument uses a scale of one to four, namely very relevant, relevant, less relevant, and irrelevant. The data analysis used the Aiken formula for content validity and Reliability Analysis between raters using ICC. The first stage of research results has found the operational definition of reactive agility tennis: the ability to move in seconds after receiving a stimulus. In addition, the "Y" shape construction design of the reactive tennis agility measuring instrument has been arranged. The second stage resulted in the contents validation of a large tennis reactive agility measuring instrument. The third stage found the reliability between raters of a large tennis reactive agility measuring instrument.